The use of patch testing for the diagnosis of contact dermatitis: an Albanian experience (Journal of Health Sciences, 2015)
Introduction: The daily increase of using chemical, aromatic and cosmetic products has been associated with significant increase in frequency of skin diseases such as eczemas and contact dermatitis (CD). The aim of this study was to evaluate the use of patch testing (PT) for the diagnosis of CD and provide current data on the frequency of sensitization to various contact allergens among patients with CD in the Albanian population.Methods: We retrospectively analyzed all consecutive patients clinically suspected for CD during the period February 2010 – February 2011, in the outpatient setting. PT was done using Baseline European Series consisting of 31 allergens. Risk factors (age, gender, occupation and place of residence) and sensitization to various contact allergens were evaluated. Results: In total, 193 patients clinically suspected for CD were included in the study and underwent PT. The highest prevalence of CD was found in the age-group of 31-40 years (32.6%), with a statistically significant difference between other age-groups (X2 = 141.2, p<0.01). Positive PT results with at least one allergen were seen in 144 (74.6 %) patients suspected for CD. The two most common allergens were nickel and potassium dichromate. Construction worker and hairdresser were the most affected professions. Females had a chance of 1.8 times higher for having a positive patch test result compare to males (OR = 1.8; 95% CI 0.91 – 3.39).Conclusion: Determination of allergens that cause contact dermatitis is a necessity not only to confirm the correct diagnosis, but also for the qualitative treatment and prevention of the disease. Patch testing, even though an old method, still remain a valuable and non-invasive approach to determine the causes of contact dermatitis.